(untitled) (American Journal of Education and Technology, 2024)
This research shed light upon the various recreational values involved and how recreational trips matter in the growth and development of students. The primary school students, specifically the female students, were targeted here, and the discussions were carried out regarding how these recreational trips influenced the performance of the various candidates. This descriptive research was conducted on a group of 797 participants from the government and private schools. The findings of the study indicate that a majority of 51.7% members were found to opt for five or less training courses. And 44.8% of all the members were among those who were interested in Educational courses.